Pengembangan Pola Kemitraan dalam Menunjang Saluran Distribusi Beras di Kabupaten Sidenreng Rappang - Aksal Mursalat (AGRIMOR, 2021)
Sidenreng Rappang Regency is one of the providers of rice in South Sulawesi Province in supporting food self-sufficiency in Indonesia. However, there are several problems, especially in the rice distribution channel in Sidenreng Rappang Regency, namely the distribution mechanism that is not regulated in regional policies so that the distribution channel becomes longer which has the potential to cause price play practices between marketing agencies involved in the distribution channel. One of the efforts to improve the distribution performance of agricultural products is by implementing a partnership pattern. However, the partnership pattern that runs in the rice distribution channel in Sidenreng Rappang Regency is still not optimal because the existing partnership pattern has involved a large number of marketing agencies, which indicates that the marketing channel is very inefficient. The purpose of this study is to identify partnership patterns by analyzing internal and external environmental factors in rice distribution channels and formulating alternative strategies for developing partnership patterns in rice distribution activities in Sidenreng Rappang Regency. This research was conducted in Sidenreng Rappang Regency which took place from September to January. The method used is observation and interviews, then the data is analyzed using the help of an Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrix followed by a SWOT matrix analysis to formulate and determine strategic priorities. The results show an alternative strategy in developing partnership patterns in supporting the performance of rice distribution in Sidenreng Rappang Regency, namely by expanding access to farmers' capital to the government or private parties, establishing partnerships with e-commerce marketing agencies, forming farmers partnerships with cooperatives, and implementing patterns. direct partnerships with large companies.